Street Performances and Poverty: A Literature Review - Lawe, Kahlila Denali; Purwanti, Tari (Sabda: Jurnal Kajian Kebudayaan, 2022)
AbstractPoverty persists as an enduring global dilemma, and Indonesia epitomizes this challenge with a significant number of its populace ensnared in its grasp. The intricate relationship between poverty and busking further underscores the pervasive nature of socio-economic struggles. The term 'buskers' refers to those who choose the streets as their stage, a phenomenon observable across the archipelago, spanning from Sabang to Merauke. However, the evolution of this community has taken an interesting trajectory over time. Beyond conventional musical renditions and sidewalk performances, contemporary Indonesian buskers have diversified their expressions, branching into novel forms of artistic representation. Yet, this transformation does not necessarily mirror prosperity. In stark contrast to their international counterparts, the socio-economic predicament faced by Indonesian buskers remains unresolved. This article delves into an exploration of pertinent literature on busking, aiming to establish correlations between this artistic pursuit and the achievement levels of Sustainable Development Goals (SDGs) 1 and 8. Specifically focusing on the DKI Jakarta Province, the inquiry seeks to unravel the intricate dynamics at play and discern potential pathways towards addressing the socio-economic challenges intertwined with the practice of busking in Indonesia.Keywords: Poverty, Buskers, Indonesia, Sustainable Development Goals (SDGs)